(untitled) - Gupta, Jatinder N. D. (Hersley, PA, 2004)
Text discusses high quality concepts and techniques closely related to organizational learning, knowledge workers, intellectual capital, and knowledge management. Includes the methodologies, systems, and approaches that are needed to create and manage knowledge based organizations. Softcover, hardcover available. DLC: Intellectual capital.
Keywords: Intellectual capital,Organizational learning,Organizational change; Management